A comparison between decay patterns of the white‐rot fungus Pleurotus ostreatus in chestnut–leaved oak (Quercus castaneifolia) shows predominantly simultaneous attack both in vivo and in vitro. Issue 4 (17th February 2017) - Bari, E.; Karim, M.; Oladi, R.; Tajick Ghanbary, M. A.; Ghodskhah Daryaei, M.; Schmidt, O.; Benz, J. P.; Emaminasab, M.
Summary: In this research, we examined decay patterns occurring in Quercus castaneifolia wood under natural conditions compared with controlled decay in vivo . Pleurotus ostreatus ‐infected oak wood was obtained from the Sari forests in the north of Iran. The species causing decay was verified as P. ostreatus using rDNA‐ITS sequencing of pure cultures from infected sapwood. In addition to P. ostreatus, two wood‐inhabiting Ascomycota, Trichoderma harzianum and T. lixii, were present. Mass loss in oak sapwood samples exposed to P. ostreatus for 60 days was around 10 per cent. Samples were prepared from both naturally decayed wood and wood decayed under controlled conditions and examined using microscopy. P. ostreatus was found to produce a simultaneous white‐rot decay pattern in both conditions.